Abnormal tyrosine metabolism in chronic cluster headache. (February 2017) - D'Andrea, Giovanni; Leone, Massimo; Bussone, Gennaro; Fiore, Paola Di; Bolner, Andrea; Aguggia, Marco; Saracco, Maria Gabriella; Perini, Francesco; Giordano, Giuseppe; Gucciardi, Antonina; Leon, Alberta
Objective: Episodic cluster headache is characterized by abnormalities in tyrosine metabolism (i.e. elevated levels of dopamine, tyramine, octopamine and synephrine and low levels of noradrenalin in plasma and platelets.) It is unknown, however, if such biochemical anomalies are present and/or constitute a predisposing factor in chronic cluster headache. To test this hypothesis, we measured the levels of dopamine and noradrenaline together with those of elusive amines, such as tyramine, octopamine and synephrine, in plasma of chronic cluster patients and control individuals. Methods: Plasma levels of dopamine, noradrenaline and trace amines, including tyramine, octopamine and synephrine, were measured in a group of 23 chronic cluster headache patients (10 chronic cluster ab initio and 13 transformed from episodic cluster), and 16 control participants. Results: The plasma levels of dopamine, noradrenaline and tyramine were several times higher in chronic cluster headache patients compared with controls. The levels of octopamine and synephrine were significantly lower in plasma of these patients with respect to control individuals. Conclusions: These results suggest that anomalies in tyrosine metabolism play a role in the pathogenesis of chronic cluster headache and constitute a predisposing factor for the transformation of the episodic into a chronic form of this primary headache.